Information and Communication Technology (ICT) and Disability. (April 2014) - Khetarpal, Abha
Disability is not inability. A disability is only actually a disability only when it prevents someone from doing what they want or need to do. Technologies and communication devices help reduce physical barriers. Information and communication technologies (ICTs) provide a model to allow people with disabilities to better integrate socially and economically into their communities by supporting personal access to information and knowledge, learning and teaching situations, personal communication and interaction and access to educational administrative procedures. When we talk about accessibility issues, removing barriers to accessing ICTs by persons with disabilities is of paramount importance. Government agencies, NGOs and private sector should all come out to remove barriers to access ICTs and work together with the stakeholders so that people with disabilities are able to live independent life.